Detection of varicella-zoster virus (VZV) DNA in clinical samples from patients with VZV by the polymerase chain reaction. - Kido, S (1991)
A polymerase chain reaction system for the detection of varicella-zoster virus was established. Of 25 nucleotides, 4 oligonucleotide pairs (regions of thymidine kinase, thymidylate synthetase, glycoprotein I, and immediate early gene) were synthesized. The first three oligonucleotide pairs could be used as primers on the basis of specific DNA amplification. Varicella-zoster virus DNA was amplified by this polymerase chain reaction system in 20 of 20 vesicle samples, 5 of 6 crusts, and 12 of 13 throat swabs collected from patients with clinical varicella.